The Effects of Parenting Styles on the Psychosocial Development of 6-11 Years Children in Buea Sub-Division of the Southwest Region of Cameroon - Esunge, Sone-Ajang Doris (Journal of Early Childhood Development and Education, 2025)
Background of study: Parenting styles play a vital role in shaping children's psychosocial development. This study explores how different parenting styles authoritative, authoritarian, and permissive affect the psychosocial development of children aged 6–11 years in Buea Sub-division, South West Region. Aims and scope of paper: The study aims to determine the extent to which each parenting style influences children’s psychosocial outcomes such as self-esteem, emotional expression, and social interaction. Methods: A survey research design was employed. A sample of 370 children and 75 parents was selected using purposive and snowball sampling techniques, respectively. Data were collected using a structured questionnaire for children and an interview guide for parents. Both descriptive and inferential statistics were used for data analysis. Result: Findings showed that authoritarian parenting style negatively affects children’s psychosocial development (R = -0.188, p = 0.014), with 34.6% of such children showing low self-esteem and social withdrawal. Permissive parenting had an even stronger negative effect (R = -0.751, p = 0.000), with 37.2% of children scoring low on psychosocial measures. Conversely, authoritative parenting significantly and positively influenced psychosocial development (R = 0.427, p = 0.000), with 85.7% of children showing high self-esteem, sociability, and self-control. Conclusion: Authoritative parenting promotes positive psychosocial outcomes in children. It is recommended that parents adopt this style to foster emotional and social well-being in children.